2017
DOI: 10.1007/s00709-017-1180-2
|View full text |Cite
|
Sign up to set email alerts
|

Early plant growth and biochemical responses induced by Azospirillum brasilense Sp245 lipopolysaccharides in wheat (Triticum aestivum L.) seedlings are attenuated by procyanidin B2

Abstract: This study analyzes the effects of procyanidin B2 on early wheat plant growth and plant biochemical responses promoted by lipopolysaccharides (LPS) derived from the rhizobacteria Azospirillum brasilense Sp245. Measurements of leaf, root length, fresh weight, and dry weight showed in vitro plant growth stimulation 4 days after treatment with A. brasilense as well as LPS. Superoxide anion (O) and hydrogen peroxide (HO) levels increased in seedling roots treated with LPS (100 μg mL). The chlorophyll content in le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The plant-growth-promotion effect of LPS has been reported so far on wheat (Triticum aestivum) treated with Azospirillum brasilense Sp245 LPS, but its effective concentration was 100 mg mL −1 [24]. LPS from PNSB in the present study was effective at 100 pg mL −1 , indicating that the LPS of PNSB had extremely high plant-growth-promoting activity.…”
Section: Discussioncontrasting
confidence: 52%
“…The plant-growth-promotion effect of LPS has been reported so far on wheat (Triticum aestivum) treated with Azospirillum brasilense Sp245 LPS, but its effective concentration was 100 mg mL −1 [24]. LPS from PNSB in the present study was effective at 100 pg mL −1 , indicating that the LPS of PNSB had extremely high plant-growth-promoting activity.…”
Section: Discussioncontrasting
confidence: 52%
“…Chávez-Herrera et al [ 28 ] examined the effects of LPS from Azospirillum brasilense Sp245 on the leaf and root development of Triticum aestivum by pot experiment, and found that both leaf and root development were promoted by LPS. The same research group reported the ROS (H 2 O 2 ) generation and plant growth promotion (leaf and root) by LPS from A. brasilense Sp245 in T. aestivum [ 85 ]. They also treated the LPS-elicited plants with catalase, which catalyzes the decomposition of hydrogen peroxide to water and oxygen, and found a decrease in H 2 O 2 content in the roots and also a decrease in the growth of seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…A. brasilense LPS are highly active in interactions with plant roots (Fedonenko et al 2001;Matora et al 1995) and in induction of plant responses (Evseeva et al 2011). Furthermore, A. brasilense Sp245 LPS can promote wheat plant growth in vitro (Vallejo-Ochoa et al 2018) and under greenhouse conditions (Chavez-Herrera et al 2018).…”
Section: Introductionmentioning
confidence: 99%